(untitled) (CIPEEX, 2025)
This study discusses the importance of verifying the lawfulness of objects in contractual relations to ensure greater legal security for the involved parties. Additionally, it addresses the legal and ethical implications of receiving stolen goods, a crime with penal consequences that directly affects the moral and ethical lives of those involved. In a scenario of increasing complexity in contractual transactions, ensuring the lawfulness of objects is essential to avoid legal disputes and protect the parties. Through the analysis of legislation, doctrine, case law, and jurisprudence, this study aims to guide not only the academic public but also the community, contributing to awareness about lawfulness in contractual relations.